2002
DOI: 10.1136/ip.8.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helmet wear on the incidence of head/face and cervical spine injuries in young skiers and snowboarders

Abstract: Purpose: To evaluate whether helmets increase the incidence and/or severity of cervical spine injury; decrease the incidence of head injury; and/or increase the incidence of collisions (as a reflection of adverse effects on peripheral vision and/or auditory acuity) among young skiers and snowboarders. Methods: During one ski season (1998-99) at a world class ski resort, all young skiers and snowboarders (<13 years of age) presenting with head, face, or neck injury to the one central medical facility at the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
2
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 26 publications
1
96
2
4
Order By: Relevance
“…13) Wearing a helmet is effective for preventing head injuries in skiers and snowboarders. 13,17) We obtained the same finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13) Wearing a helmet is effective for preventing head injuries in skiers and snowboarders. 13,17) We obtained the same finding.…”
Section: Discussionmentioning
confidence: 99%
“…13) Wearing a helmet is effective for preventing head injuries in skiers and snowboarders. 13,17) We obtained the same finding. Head wear including a helmet or knit cap protected against serious head injuries on jumping, but whether helmet use prevents injuries in snowboarders is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis, based on five wellconducted case-control studies on pedal cycle helmets in transport and recreation, have confirmed that helmets provide a 63Á88% reduction in the risk of head, brain, and severe brain injury for cyclists of all ages (Thompson, Rivara, & Thompson, 2000). In recreational skiing and snowboarding, there is solid evidence to show that using a helmet is associated with a 22Á60% reduction in head injury rates (Hagel, 2005;Macnab, Smith, Gagnon, & Macnab, 2002;Sulheim, Holme, Ekeland, & Bahr, 2006). Thus, it is strongly recommended that recreational skiers and snowboarders wear helmets.…”
Section: Preventionmentioning
confidence: 99%
“…Counter-examples also exist. For example, the introduction of helmets in snowboarding has resulted in reduced head injuries but no concomitant increase in neck injuries as would result if helmeted snowboarders took greater degrees of risk (27). A recent study examined 23,000 cyclists involved in traffic crashes and found that committing a speed-related infraction was not associated with the frequency of helmet use (28).…”
Section: Countering Opposition Tomentioning
confidence: 99%